THE HISTORY OF FIEP IN ARGENTINA (Fiep Bulletin - online, 2012)
In 1981, I attend the International Congress of Sports Medicine and Applied Science at theSheraton Hotel in the city of Buenos Aires; where I became aware of the FIEP, as first heard from Prof. PIERRESEURIN, the FIEP World President at the time. In the same conference, I talked to the first National Delegate ofFIEP Argentina, Prof. Enrique Carlos Romero Brest, who I met when I was a student of Physical Education in the2n Cordoba IPEF, 1959, and I could also talk to Professor Ramon Muros,Dr. Antonio Alcazar and Professor Mario López, all FIEP members, institution unknown to me at thattime.